Comparative evaluation of platelet-rich fibrin, mineral trioxide aggregate, and calcium hydroxide as pulpotomy agents in permanent molars with irreversible pulpitis: A randomized controlled trial - Varun Kumar; Ruchi Juneja; Jigyasa Duhan; Pankaj Sangwan; Sanjay Tewari (Contemporary Clinical Dentistry, 2016)
Background: Pulpotomy has been proposed as an alternative for the management of irreversible pulpitis in permanent molars with closed apices. Aim: To compare the performances of calcium hydroxide (CH), mineral trioxide aggregate (MTA), and platelet-rich fibrin (PRF) as pulpotomy agents in mature permanent molars with irreversible pulpitis. Materials and Methods: Fifty-four permanent mandibular molars with carious exposure and symptoms of irreversible pulpitis were randomly allocated to three groups, and full pulpotomy was performed using CH,MTA, or PRF as pulpotomy agents. Pain intensity was recorded using numeric rating scale score at baseline, 24 h, 7 days, 6 months, and 1 year. Clinical and radiographic assessments were done at 6 months and 1 year. Statistical Analysis: Kruskal–Wallis test and Friedman test were used for intergroup and intragroup comparison of pain scores, respectively. The radiographic outcomes between the three study arms were compared using Chi-square test. Results: Clinical success rate was 94.4% at 7 days, which dropped to 85.4% at 12 months. All three agents were equally effective in providing pain relief at all the intervals tested, with no significant difference between them (P > 0.05 at all intervals). However, at 6 months and 12 months, 26.2% and 52.4% teeth depicted slight widening of periodontal ligament space. No significant difference was observed between the radiographic success rates observed with the three groups (P = 0.135 at 6 months, 0.717 at 12 months). Conclusion: Pulpotomy exhibited a high clinical success rate in mature molars with irreversible pulpitis and selection of biomaterial did not affect its outcome.